2022
DOI: 10.1055/s-0042-1744541
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Thromboprophylaxis with Heparins Following Intracerebral Hemorrhage

Abstract: Background The efficacy and safety of pharmacological thromboprophylaxis in patients with intracerebral hemorrhage (ICH) remains unclear. Methods A literature search was performed to collect studies comparing the effect of thromboprophylaxis in patients with ICH. The primary endpoints were deep vein thrombosis (DVT), pulmonary embolism (PE), and hematoma expansion or rebleeding. A meta-analytic approach was employed to estimate the relative risk (RR) by fitting fixed-effects (FE) and random-effects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, pharmacological thromboprophylaxis (RR: 0.33, 95% CI: 0.19–0.57 for the fixed-effects model; RR: 0.37, 95% CI: 0.21–0.66 for the random-effects model) was associated with a lower risk of PE without any heterogeneity ( I 2 = 0%), with the PI substantially overlapping the estimates (CI: 0.20–0.69), strengthening the results of the meta-analysis. 16 Moreover, pharmacological thromboprophylaxis was not associated with increased risk for hematoma expansion or rebleeding (RR: 0.75, 95% CI: 0.48–1.18 for the fixed-effects model; RR: 0.80, 95% CI: 0.49–1.30 for the random-effects model), with no heterogeneity ( I 2 = 0%) and overlapping PI. Also, a trend of reduced mortality was identified in patients treated with pharmacological thromboprophylaxis (RR: 0.82, 95% CI: 0.65–1.03 for fixed-effects model; RR: 0.83, 95% CI: 0.66–1.04 for the random-effects model; I 2 = 0%; PI: 0.60–1.15).…”
Section: Tablementioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, pharmacological thromboprophylaxis (RR: 0.33, 95% CI: 0.19–0.57 for the fixed-effects model; RR: 0.37, 95% CI: 0.21–0.66 for the random-effects model) was associated with a lower risk of PE without any heterogeneity ( I 2 = 0%), with the PI substantially overlapping the estimates (CI: 0.20–0.69), strengthening the results of the meta-analysis. 16 Moreover, pharmacological thromboprophylaxis was not associated with increased risk for hematoma expansion or rebleeding (RR: 0.75, 95% CI: 0.48–1.18 for the fixed-effects model; RR: 0.80, 95% CI: 0.49–1.30 for the random-effects model), with no heterogeneity ( I 2 = 0%) and overlapping PI. Also, a trend of reduced mortality was identified in patients treated with pharmacological thromboprophylaxis (RR: 0.82, 95% CI: 0.65–1.03 for fixed-effects model; RR: 0.83, 95% CI: 0.66–1.04 for the random-effects model; I 2 = 0%; PI: 0.60–1.15).…”
Section: Tablementioning
confidence: 95%
“…Also, the additional analyses showed that among randomized controlled trials, patients receiving LMWH/UFH were associated with a lower risk of hematoma expansion or rebleeding (RR: 0.53, 95% CI: 0.28–0.99; I 2 = 0%; p = 0.13 for test for subgroup differences). 16 Finally, it is noted that there was a significant overall risk of bias for most of the studies enrolled, with eight studies being at high risk of bias.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations